PENGEMBANGAN MEDIA POP-UP GAMBAR SERI PADA MATA PELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS II SD - Amarta, Lady; Marini, Arita; Hadi, Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a series picture Pop-Up Card learning media to improve speaking skills of second-grade elementary school students in Indonesian Language subject. This research uses Research and Development (R&D) method with the ASSURE development model, implemented through four stages: Analyze Learners, State Objectives, Select Methods, Media and Materials, and Utilize Media and Materials. The product developed is a series picture card in Pop-Up format, sized 29.7 × 42 cm, featuring four sequential story pictures with themes relevant to students' daily lives. Validation was conducted by a material expert and a media expert, both of whom are second-grade elementary school teachers. The results showed that the material expert validation reached 93.75% (Very Valid category) and the media expert validation reached 95% (Very Valid category), with a combined total of 94.375% (Very Valid). A small-group trial involving 6 students showed a student response rate of 80% (Valid category). These results indicate that the series picture Pop-Up Card media is feasible to use as a learning medium for speaking skills in Indonesian Language learning for second-grade elementary school students.